2013
DOI: 10.1108/ijdrbe-08-2012-0026
|View full text |Cite
|
Sign up to set email alerts
|

Heat wave adaptations for UK dwellings and development of a retrofit toolkit

Abstract: Purpose – Dwelling retrofit strategies generally concentrate on measures to reduce energy use and carbon emissions. However, climate change projections predict increases in both the frequency and severity of extreme weather events, including heat waves. It is predicted that by the 2040s severe heat waves similar to the European one in August 2003 may be expected to occur every year. Future guidance therefore needs to combine mitigation with adaptation in order to provide safe and comfortable dwellings, whilst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…14 Solid wall insulation was found to be particularly dangerous for increasing the overheating risk, consistent with previous studies, 8,27 whilst airtightening was found to be another significant contributor to overheating risk. In addition, this paper demonstrates the risks to occupants from retrofits where additional compensatory ventilation is provided.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…14 Solid wall insulation was found to be particularly dangerous for increasing the overheating risk, consistent with previous studies, 8,27 whilst airtightening was found to be another significant contributor to overheating risk. In addition, this paper demonstrates the risks to occupants from retrofits where additional compensatory ventilation is provided.…”
Section: Discussionsupporting
confidence: 78%
“…A large monitoring study of UK dwellings found that flats and modern homes have an increased risk of overheating, 6 similar to the results predicted by modelling studies. 7 Building characteristics such as built form and building fabric design, air change rate, the storey level of flats in multifamily buildings and orientation [7][8][9] ; local environment of the building (including shading, microclimate and urban heat island) 7,10,11 and occupant behaviour 12 may all influence the risk of overheating. The geographical location of dwellings within the UK may also have an impact on both absolute overheating risk and the relative risk of overheating amongst different dwelling types.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, extensions, conservatories, new window systems and other adaptations all conspire to reduce the prospects for adequate ventilation and increase the risk of summertime overheating. Whilst the potential for exacerbating overheating risk is now recognized (DECC, 2015;Porritt, Cropper, Shao, & Goodier, 2013), the matter is paid little attention in practice.…”
Section: Why Is Overheating a Problem And Why Now?mentioning
confidence: 99%
“…Comprehensive studies on the assessment of different retrofitting techniques, such as a retrofitting toolkit from UK [69] are few in number. The efficiency of mitigation techniques is rarely compared across different climates, despite the importance of climate specific design [23].…”
Section: Precinct Retrofitting For Heatwave Resiliencementioning
confidence: 99%